Institutional Factors Influencing Bilingual Education: A Primary School Perspective from Ghana - Fenuku, Samson Dodzi (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
This study examines the institutional factors influencing the effectiveness of bilingual education in primary schools within the Ledzokuku Municipality of Accra, Ghana. This study uses a mixed methods approach, and the research explores the interplay between teacher training, resource availability, administrative support, and community involvement in the success of bilingual education programs. A case study at Adom Primary School provides in-depth insights into the experiences of educators, administrators, and parents, while a survey of 200 educators and administrators offers a broader perspective. Qualitative findings emphasize the need for comprehensive teacher training and the critical role of community support in supplementing school resources. Teachers desire more extensive training to deliver instruction confidently in a second language. The case study reveals the significant impact of community involvement in overcoming resource limitations, suggesting local engagement as a strategic asset for bilingual education. Quantitative results corroborate these insights, showing significant positive correlations between teacher training hours, resource availability, and program effectiveness. Regression analysis indicates that teacher training and resource availability are significant predictors of program effectiveness, underscoring the need for targeted investments in these areas. The study identifies challenges such as a shortage of qualified bilingual teachers, resource scarcity, and the complexity of aligning language policies with community expectations. Recommendations include developing robust teacher training programs, increasing resource allocation, and fostering community-school partnerships. This research contributes to the literature by providing a nuanced understanding of the institutional factors impacting bilingual education in a Ghanaian context, with implications for educational policy and practice.